Assessment of the Acute Phase Response in Healthy and Injured Southern White Rhinoceros (Ceratotherium simum simum) - Hooijberg, Emma H.; Cray, Carolyn; Steenkamp, Gerhard; Buss, Peter; Goddard, Amelia; Miller, Michele (Frontiers in Veterinary Science, 2020)
Acute phase reactants (APRs) have not been investigated in white rhinoceros. This study aimed to identify clinically useful APRs in this species. Reference intervals (RIs) were generated for albumin, fibrinogen, haptoglobin, iron and serum amyloid A (SAA) from 48 free-ranging animals, except for SAA (n=23). APR concentrations between healthy animals and those with tissue injury (inflammation) (n=30) were compared. Diagnostic performance was evaluated using receiver-operator characteristic (ROC) curve and logistic regression analyses. RIs were: albumin 18-31 g/L, fibrinogen 1.7-2.9 g/L, haptoglobin 1.0-4.3 g/L, iron 9.7-35.0 mol/L, SAA <20 mg/L. Iron and albumin were lower and fibrinogen, haptoglobin and SAA higher in injured versus healthy animals. Iron showed the best diagnostic accuracy followed by fibrinogen, albumin, haptoglobin and SAA. Iron ≤ 15.1 mol/L and haptoglobin > 4.7 g/L were significant predictors of inflammatory status and together correctly predicted the clinical status of 91% of cases. SAA > 20 mg/L had a specificity of 100%. In conclusion, albumin and iron are negative and fibrinogen, haptoglobin and SAA positive APRs in the white rhinoceros. The combination of iron and haptoglobin had an excellent diagnostic accuracy for detecting inflammation.